Vax genes ventralize the embryonic eye - Mui, Stina H. (Cold Spring Harbor Laboratory Press, 2005)
The vertebrate retina and optic nerve are strikingly different in terms of their size, organization, and cellular diversity, yet these two structures develop from the same embryonic neuroepithelium. Precursor cells in the most ventral domain of this epithelium give rise only to the astrocytes of the optic nerve, whereas immediately adjacent, more dorsal precursors give rise to the myriad cell types of the retina. We provide genetic evidence that two closely related, ventrally expressed homeodomain proteins—Vax1 and Vax2—control this neuroepithelial segregation. In the absence of both proteins, we find that the optic nerve is transformed in its entirety into fully differentiated retina. We demonstrate that this transformation results from the loss of ventralizing actvity in the developing eye field, and that ventralization is mediated, at least in part, via Vax repression of the Pax6 gene, a potent inducer of retinal development.